The Effect Of Profitability, Liquidity, Leverage On Bond Rating Of Financial Companies - Suryadi Hung; Ella Silvana Ginting; Sherly Joe (Institute of Computer Science (IOCS), 2021)
This research was ain determine and analyze the effect of Simultaneous and Partial on Current Ratio, Debt to Equity Ratio, and Return On Assets on Bond Ratings in financial sector companies on the Indonesia Stock Exchange for the 2016-2019 period. The population of this reserach is the financial sector companies as many as 94 companies. The sampling method used purposive sampling, and the number of samples obtained was 18 companies. This type of research is quantitative descriptive using multiple linear regression analysis method. The results of this research show that the variables Current Ratio, Debt to Equity Ratio, and Return On Assets simultaneously have a significant effect on the Bond Rating of financial sector companies on the Indonesia Stock Exchange (IDX) in 2016-2019. Partially, Current Ratio, Debt to Equity Ratio, and Return On Assets have a significant positive effect on Bond Ratings for financial sector companies on the Indonesia Stock Exchange (IDX) in 2016-2019.